From infancy to toddlerhood: A 3D analysis of facial asymmetry in children with and without orofacial clefts - Martinková, Katarína; Kožejová Jaklová, Lenka; Kočandrlová, Karolina; Borský, Jiří; Dupej, Ján; Morávek, Alexander; Velemínská, Jana (Clinical oral investigations, 2025)
OBJECTIVES: This study investigates facial directional asymmetry (DA) in early childhood. Using 3D imaging, it aims to assess the DA progression in healthy controls and children with unilateral cleft lip (CL) and unilateral cleft lip and palate (UCLP) following early neonatal cheiloplasty and palatoplasty. MATERIALS & METHODS: The sample consisted of 105 children (groups: cleft 42, control 63) aged 0.2-2 years. DA was analysed using geometric morphometrics, including 3D landmark-based and polygonal mesh analyses. Multivariate statistics were used for assessing DA significance and age group differences. RESULTS: Controls showed no DA in landmarks and only mild protrusion of the right hemiface, increasing with age. In groups with cleft, DA was more pronounced in UCLP and especially in the middle of the face. While older UCLP children showed more asymmetrical faces, DA in children with CL became more comparable to that in controls with increasing age. Older children showed no statistical difference between control and CL in the landmark and polygonal maps parts. CONCLUSIONS: After surgical treatment, a DA pattern was identified, and it was specific for both cleft types and age categories. For both diagnoses, the most notable feature is the protrusion at the cleft site, likely related to post-surgical scarring, but in the UCLP group, it is also the hypoplastic nasal wing and a growth insufficiency of the cheek on the cleft side. CLINICAL RELEVANCE: 3D methodologies provide insight into asymmetry progression and surgical outcomes, supporting improved cleft management for enhanced aesthetic and functional results.
Keywords: Imaging, Three-Dimensional; Cleft Lip; Humans; Infant; Case-Control Studies; kojenec; studie případů a kontrol; Female; lidé; Geometric morphometrics; Infancy & toddlerhood; předškolní dítě; Facial Asymmetry; ženské pohlaví; Facial development with cleft; Male; Directional asymmetry; Polygonal mesh analyses; Cleft Palate; asymetrie obličeje; zobrazování trojrozměrné; rozštěp patra; rozštěp rtu; mužské pohlaví; Child, Preschool; 3D landmarks-based methods